IL-8 producing cells in patients with Behcet's disease - (:unkn) unknown (CLINICAL & EXPER RHEUMATOLOGY, 2000)
Objective IL-8 is thought to be the principal chemokine responsible for neutrophil activation and tissue infiltration in patients with Behcet's disease (BD). In various studies serum levels of IL-8 were reported to be increased. Methods IL-8 mRNA was purified from both peripheral whole blood samples and separated lymphocytes, granulocytes and monocytes of patients with BD and compared to that from healthy (HC) and disease controls. IL-8 sequences were revealed by PCR amplification using appropriate sequence-specific primers, mRNA levels were determined semi-quantitatively using an image analyser in comparison with beta-actin. Results Although the differences did not reach statistical significance, BD patients tended to have higher IL-8 mRNA levels compared to HC in whole blood samples (2.0 +/- 1.4 vs 1.5 +/- 1.2) as well as in their lymphocytes (2.7 +/- 1.6 vs 1.5 +/- 0.9). No differences were observed between BD and HC in monocyte or granulocyte IL-8 mRNA levels. Conclusion Our results suggest that the cellular source of IL-8 is diverse in BD with a possible major contribution by lymphocytes.
Keywords: Behcet's disease; IL-8; mRNA; INTERLEUKIN-8; ALPHA; INTERFERON; TNF